ASSISTANCE OF QUALITY CONTROL OF YOGHURT PRODUCTION PROCESS - Hastuti, Arti; Amanda Lestari, Tiara; Ali Fulazzaky, Mohamad (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2022)
This Community Service activity aims to provide knowledge related to quality control aspects through assistance in quality control of the yogurt production process in the yogurt SME business actors Sukabirus, Megamendung-Bogor District. The marketing of yogurt is quite extensive while quality control does not yet exist, it is hoped that the quality of the products marketed is of good quality and can compete in the market. Assistance in quality control of final product analysis on pH parameters and brix degrees. Analysis of the data on the quality control of the final product using a simple Microsoft Excel analysis whose results are compared with the competitor's products and SNI. The results of this yogurt quality control assistance show that the pH value of the yogurt flavor variant in yogurt SMEs is around 3.5-3.8 and the brix degree value is 13.5%. Prior to the quality control assistance, yogurt SMEs did not know the quality of the products produced. After the assistance of quality control in the analysis of the final product, the yogurt produced meets SNI standards, there are no damaged products because the production of yogurt is adjusted to market demand, the yogurt produced is fresh and of good quality so that it can compete in the market. Keywords: Quality Control Assistance, yogurt SMEs.